Customer Satisfaction on the Use of QR Codes For Frozen Shrimp Products at PT. Kelola Mina Laut Based on the Theory of Stimulus Organism Response - Dedi Kadhafi; Moh. Agung Surianto (Indonesian Vocational Research Journal, 2022)
Background – Customer satisfaction is very important for business continuity in a company. PT. Kelola Mina Laut (KML) is a fisheries industry that implements a defensive strategy for its marketing, namely by applying a QR code to traceability information of frozen shrimp products that provide added value for its customers. Aim – Identify and analyze customer satisfaction on the use of QR codes for frozen shrimp products at KML based on S-O-R theory (Usefulness, Acceptability, Feasibility, Perceived flow, and Customer Satisfaction). Design / methodology / approach – This study uses 7 (seven) people as informants, who are KML customers, and then analyzed using Miles and Huberman Analysis. Findings – Customer satisfaction on the S-O-R theory was tested when the customer said he was very satisfied using this QR Code system, the customer's feeling when using this traceability system was easy and positive when using the QR code. Customers think this system is feasible to use and can be recommended to other customers. Research implication – The results of this study are a means for researchers to add insight and knowledge about traceability systems using QR codes at KML shrimp processing unit in an effort to increase customer satisfaction. Limitations – The QR code used contains information on the frozen shrimp product traceability system. The theoretical basis used is the S-O-R theory. The research location is in the KML Gresik, and test the validity of the data in this study using Source Triangulation.